2020
DOI: 10.28949/bilimname.673337
|View full text |Cite
|
Sign up to set email alerts
|

İran Bankacılık Sistemi Üzerine Bir Araştırma: Sorunlar ve Çözüm Önerileri

Abstract: Iran is one of the two countries that have full-fledged Islamic banking in their banking systems. Although there are many criticisms about the operation of the Islamic system in Iran, this country has the greatest proportion of Islamic banking assets in the global Islamic financial system. Islamic banking in Iran, as one of the milestones of the reorganization of Iranian society after the Iranian Revolution, continues its operation by the contracts which take their roots from the economic and social factors. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…According to Öztekin and Şahin (2020), a good roadmap is needed in science journalism, as exaggerated inflated claims, scientific abuses, ethical violations, conflicts of interest can destroy scientific realities. Erdoğan's (2007) study also reveals that there are hardly any professional science reporters in the media. Therefore, it has recently emerged that an increasing portion of science news published in Switzerland is based on press releases provided by the university (Vogler and Schäfer, 2020).…”
Section: Newspapers and Science Literacymentioning
confidence: 91%
See 1 more Smart Citation
“…According to Öztekin and Şahin (2020), a good roadmap is needed in science journalism, as exaggerated inflated claims, scientific abuses, ethical violations, conflicts of interest can destroy scientific realities. Erdoğan's (2007) study also reveals that there are hardly any professional science reporters in the media. Therefore, it has recently emerged that an increasing portion of science news published in Switzerland is based on press releases provided by the university (Vogler and Schäfer, 2020).…”
Section: Newspapers and Science Literacymentioning
confidence: 91%
“…Mass media, especially newspapers, are important social institutions in a link with the country's cultural, economic, and political state. Gathering and evaluating information about these institutions, integrating them into theoretical structures, and understanding the nature of these institutions through theoretical explanations are very important in academic terms (Erdoğan, 2007). Over the years, it has been observed that science and scientific research have an increasing impact, both directly and indirectly, on public life.…”
Section: Introductionmentioning
confidence: 99%